Statistical analysis of the stability number adjustment factors and implications for underground mine design. (September 2016) - Vallejos, J.A.; Delonca, A.; Fuenzalida, J.; Burgos, L.
Highlights: Evaluation of the significance of the adjustment factors on the Mathews method. Use of a contingency matrix and a performance metrics analysis. Proposal of a new rock stress factor A less conservative than the original one. Other factors did not improve the significance of the method compared to the original. Proposed rock stress factor leads to larger size stopes.